Hobbes and the law / edited by David Dyzenhaus and Thomas Poole. - Dyzenhaus, David; Poole, Thomas (Thomas M.) (Cambridge University Press, 2012)
Hobbes's political thought provokes a perennial fascination. It has become particularly prominent in recent years, with the surge of scholarly interest evidenced by a number of monographs in political theory and philosophy. At the same time, there has been a turn in legal scholarship towards political theory in a way that engages recognisably Hobbesian themes, for example the relationship between security and liberty. However, there is surprisingly little engagement with Hobbes's views on legal theory in general and on certain legal topics, despite the fact that Hobbes devoted whole works to legal inquiry and gave law a prominent role in his works focused on politics. This volume seeks to remedy this gap by providing the first collection of specially commissioned essays devoted to Hobbes and the law.